Should Countries Set an Explicit Health Benefits Package? The Case of the English National Health Service() - Smith, Peter C (Value Health, 2017)
BACKGROUND: A fundamental debate in the transition towards universal health coverage concerns whether to establish an explicit health benefits package to which all citizens are entitled, and the level of detail in which to specify that package. At one extreme, the treatments to be funded, and the circumstances in which patients qualify for the treatment, might be specified in great detail, and be entirely mandatory. This would make clinicians little more than automata, carrying out prescribed practice. At the other extreme, priorities may be expressed in very broad terms, with no compulsion or other incentives to encourage adherence. OBJECTIVES: The paper examines the arguments for and against setting an explicit benefits package, and discusses the circumstances in which increased detail in specification are most appropriate. METHODS: The English National Health Service is used as a case study, based on institutional history, official documents and research literature. RESULTS: Although the English NHS does not explicitly specify a health benefits package, it is in some respects establishing an ‘intelligent’ package, based on instruments such as an essential medicines list, clinical guidelines, provider payment and performance reporting, which acknowledges gaps in evidence and variations in local resource constraints. CONCLUSIONS: Further moves towards a more explicit specification are likely to yield substantial benefits in most health systems. Considerations in determining the ‘hardness’ of benefits package specification might include the quality of information about the costs and benefits of treatments, the heterogeneity of patient needs and preferences, the financing regime in place, and the nature of supply side constraints.